Organization and Evolution of a Gene-Rich Region of the Mouse Genome: A 12.7-Mb Region Deleted in the Del(13)Svea36H Mouse - Mallon, Ann-Marie; Wilming, Laurens; Weekes, Joseph; Gilbert, James G.R.; Ashurst, Jennifer; Peyrefitte, Sandrine; Matthews, Lucy; Cadman, Matthew; McKeone, Richard; Sellick, Chris A.; Arkell, Ruth; Botcherby, Marc R.M.; et al. (Genome Research, 2004)
Del(13)Svea36H (Del36H) is a deletion of ∼20% of mouse chromosome 13 showing conserved synteny with human chromosome 6p22.1-6p22.3/6p25. The human region is lost in some deletion syndromes and is the site of several disease loci. Heterozygous Del36H mice show numerous phenotypes and may model aspects of human genetic disease. We describe 12.7 Mb of finished, annotated sequence from Del36H. Del36H has a higher gene density than the draft mouse genome, reflecting high local densities of three gene families (vomeronasal receptors, serpins, and prolactins) which are greatly expanded relative to human. Transposable elements are concentrated near these gene families. We therefore suggest that their neighborhoods are gene factories, regions of frequent recombination in which gene duplication is more frequent. The gene families show different proportions of pseudogenes, likely reflecting different strengths of purifying selection and/or gene conversion. They are also associated with relatively low simple sequence concentrations, which vary across the region with a periodicity of ∼5 Mb. Del36H contains numerous evolutionarily conserved regions (ECRs). Many lie in noncoding regions, are detectable in species as distant as Ciona intestinalis, and therefore are candidate regulatory sequences. This analysis will facilitate functional genomic analysis of Del36H and provides insights into mouse genome evolution.
10.1101/gr.2478604